2000
DOI: 10.2307/1602828
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Childhood Unintentional Injuries and the Value of Prevention

Abstract: Cost data are useful in comparing various health problems, assessing risks, setting research priorities, and selecting interventions that most efficiently reduce health burdens. Using analyses of national and state data sets, this article presents data on the frequency, costs, and quality-of-life losses associated with unintentional childhood injuries in 1996. The frequency, severity, potential for death and disability, and costs of unintentional injury make it a leading childhood health problem. Unintentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
102
0
10

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(113 citation statements)
references
References 19 publications
(20 reference statements)
1
102
0
10
Order By: Relevance
“…In this way the price of effective prevention can be shown to be economically worthwhile. 108 According to a study by Kopjar,83 the average direct medical cost per injury was estimated to NOK 3,807 (1994 price level) or US$ 163. The cost per hospitalized patient was NOK 24,831 and per outpatient NOK 1,011.…”
Section: Economic Consequences Of Injurymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way the price of effective prevention can be shown to be economically worthwhile. 108 According to a study by Kopjar,83 the average direct medical cost per injury was estimated to NOK 3,807 (1994 price level) or US$ 163. The cost per hospitalized patient was NOK 24,831 and per outpatient NOK 1,011.…”
Section: Economic Consequences Of Injurymentioning
confidence: 99%
“…Because of the high frequency of small injuries that keep children at home from school for a few days with one of their parents, the total work loss for the adult is a major cost for society. Using analysis of US national and state datasets, Miller et al 108 found that childhood injuries accounted for approximately 15% of medical spendings from ages 1-19. Fatal injuries involved less than 1% of all injuries in 1996, but accounted for more than 17% of injury related costs.…”
Section: Economic Consequences Of Injurymentioning
confidence: 99%
“…Over 10 million children annually require hospital care for the evaluation and treatment of traumatic injuries and the cost of pediatric trauma is estimated to be approximately $14 billion in lifetime medical spending [1]. In light of its overall physical, emotional and financial impact, pediatric injury is considered a major public health problem in the United States [2].…”
Section: Introductionmentioning
confidence: 99%
“…Por esta raz贸n, las intervenciones para prevenir accidentes infantiles deben incluir cambios sociales y ambientales, sin olvidar los cam-bios de conducta en el ni帽o, en la familia y los cambios en la exposici贸n a productos peligrosos (Damashek y Peterson, 2002;Dilillo, Perterson y Farmer, 2002;Girasek y Gielen, 2003;Towner, Carter y Hayes, 1998;Towner, Dowswell y Jarvis, 2001;Towner y Dowswell, 2002). Algunos autores se帽alan que la mayor铆a de las lesiones involuntarias de los ni帽os/as se podr铆an prevenir adoptando algunas medidas que supondr铆an unos gastos inferiores a los que se destinan al tratamiento de las mismas y a sus secuelas (Miller, Romano y Spice, 2000). La mayor铆a de las lesiones que sufren los ni帽os/as podr铆an ser prevenidas si se coordinaran una educaci贸n efectiva, el dise帽o de art铆culos protectores, una legislaci贸n apropiada y la implantaci贸n de estrategias de supervisi贸n para asegurar la aplicaci贸n de medidas preventivas (Bruce y McGrath, 2005;Dannenberg y Fowler, 1998;Dowd, Keenan y Bratton, 2002;Dowswell, Towner, Simpson y Jarvis, 1996;Johnston y Rivara, 2003;Tremblay y Peterson, 1999;Rivara, 2002).…”
unclassified